Trading Under Preferential Market Access Provision: Assessment of the Erosion of Preference Margins for Nepal’s Export with India - Shakya, Bijendra Man (Economic Journal of Nepal, 2014)
The role of non-reciprocal preferential market access for Nepal’s exports to India is crucial to the bilateral trade relations between these two neighbouring countries. It took a great deal of time and efforts to relax the rules of origin for Nepal to maximize the preference utilization, but after the 1996 trade treaty Nepal had virtually free trade with India. Consequently, Nepal experienced rapid growth in exports to India, including an emergence of new manufacturing products. However, the process of simplifying the rules of origin took place only as India reduced the MFN tariffs that apply to its other trading partners. That eroded the preference margins for Nepalese exports to India, adversely affecting the advantage Nepal had previously experienced and reducing the benefits of the rules of origin simplification. This study examines this erosion of preference margins and its impact on Nepal’s export to India, considering the latter’s trade reform policy, which has been expedited particularly between 1995 and 2005. During that period, Nepal’s preference was reduced for a margin between 40-70 percent for its major exports to India. The study reveals that a hypothesized 40 percent cut in India’s MFN tariff rates has a substantial impact on the exports of key products from Nepal to India (even when low export elasticity is assumed). Some key products which are found to be most at risk are those having an influential role in Nepal’s overall exports to India. Yet Nepal could maximize the preference utilization by overcoming procedural complications and improving its supply capacity.The Economic Journal of Nepal, Vol. 34, No. 1, January - March 2011 (Issue N0. 133)Uploaded date: 3/27/2014